2016
DOI: 10.18632/oncotarget.13921
|View full text |Cite
|
Sign up to set email alerts
|

Berberine augments ATP-induced inflammasome activation in macrophages by enhancing AMPK signaling

Abstract: The isoquinoline alkaloid berberine possesses many pharmacological activities including antibacterial infection. Although the direct bactericidal effect of berberine has been documented, its influence on the antibacterial functions of macrophages is largely unknown. As inflammasome activation in macrophages is important for the defense against bacterial infection, we aimed to investigate the influence of berberine on inflammasome activation in murine macrophages. Our results showed that berberine significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The roles of BBR on pyroptosis may vary in different diseases. Li et al (2017) discovered that BBR significantly increased ATP-induced pyroptosis and increased the release of caspase-1, p10, and IL-1b in macrophages. A research in 2016 (Chu et al, 2016) revealed that BBR could induce pyroptosis in HepG2 cells via activating caspase-1.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of BBR on pyroptosis may vary in different diseases. Li et al (2017) discovered that BBR significantly increased ATP-induced pyroptosis and increased the release of caspase-1, p10, and IL-1b in macrophages. A research in 2016 (Chu et al, 2016) revealed that BBR could induce pyroptosis in HepG2 cells via activating caspase-1.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse BMDMs were differentiated as reported previously ( 21 , 39 ). Briefly, mice were sacrificed and bone marrows were collected from the femurs.…”
Section: Methodsmentioning
confidence: 99%
“…Cell death was measured by PI incorporation as described previously ( 39 , 40 ). Cells were cultured in 24-well plates and primed with 500 ng/ml LPS in Opti-MEM for 4 h. Subsequently, cells were treated with indicated concentrations of baicalin in Opti-MEM for 1 h followed by stimulation with ATP (3 mM) for 30 min or nigericin (10 µM) for 1 h. The cells were stained with PI solution (2 µg/ml PI plus 5 µg/ml Hoechst 33342) for 10 min at room temperature and observed immediately by live imaging using Zeiss Axio Observer D1 microscope equipped with a Zeiss LD Plan-Neofluar 20×/0.4 Korr M27 objective lens (Carl Zeiss MicroImaging GmbH, Göttingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…As the number of patients with metabolic diseases continues to rise, it is essential to find a way to treat this diseases. And current research shows that berberine can play an important role in the treatment of nonalcoholic fatty liver through its anti-inflammatory mechanisms and in metabolism by inducing the activation of the AMPK pathway [37][38][39][40]. So it can be speculated that this will be one of the focus of future development.…”
Section: Research Frontiersmentioning
confidence: 98%